ANALISIS DAMPAK PENGGEMBALAAN SAPI DI TPA (Studi Kasus di TPA Piyungan – Yogjakarta - Wahyono, Sri (Jurnal Teknologi Lingkungan, 2010)
The end of municipal solid waste operations is landfill. Almost all of the Indonesia city’s landfills use the open dumping system. Generally, wastes dumped in the landfill are dominated by organic materials that potentially used for cow feeding. So that, in some landfills there are cow pasturing with the low cost operation related to the free feeding materials. According to UU No 18/2008, in the year of 2013 open dumping landfill is prohibited operate changed by sanitary landfill. Related to this change, the cow pasturingin landfill will be affected. So that the cow pasturing in landfill need to be assessed in the aspect of waste reduction, economic values, landfill operation, social conflict, and safety cow meat. The goals of this study are assessing positive and negative impacts from cow pasturing in the Piyungan Landfill, Yogjakarta. Research methods used are references study, interview, counting the cow and direct investigation of landfill operation. This study concluded that cow pasturing in landfill has positive impacts for waste reductionand increasing economic level of people live in surrounds of landfill. Unfortunately, the cow pasturing has also negative impact such as disturbing daily landfill operation, high potent social conflict during landfill rehabilitation, and high content of some heavy metals in the cow organ. Based on those impacts, the policy of the cow pasturing has to be reviewed because of the importance of sanitary landfill operation in the near future andthe issue of safely consuming meat free from heavy metals.Key Words: landfill, waste, cow pasturing